Method of Hierarchical QoS-Routing in SoftwareDefined Networks - Лемешко, О. В.; Євдокименко, М. О.; Єременко, О. С. (ХНУРЕ, 2020)
In the paper, the method of hierarchical QoS based inert-domain routing in Software-Defined Networks has been presented. The novelty of the method is that the obtained routing solutions have to ensure the normalized Quality of Service under indicators of average transmission rate and end-to-end average packet delay. Numerical research has been conducted with the aim of confirming the workability and effectiveness of the method by providing a normalized QoS under the finite number of iterations that help to decrease the amount of overall service traffic.
Keywords: inter-domain routing; hierarchical coordination; Quality of Service; end-to-end delay; SDN